2020
DOI: 10.3390/v12101120
|View full text |Cite
|
Sign up to set email alerts
|

A Novel RNA Virus, Macrobrachium rosenbergii Golda Virus (MrGV), Linked to Mass Mortalities of the Larval Giant Freshwater Prawn in Bangladesh

Abstract: Mass mortalities of the larval stage of the giant freshwater prawn, Macrobrachium rosenbergii, have been occurring in Bangladesh since 2011. Mortalities can reach 100% and have resulted in an 80% decline in the number of hatcheries actively producing M. rosenbergii. To investigate a causative agent for the mortalities, a disease challenge was carried out using infected material from a hatchery experiencing mortalities. Moribund larvae from the challenge were prepared for metatranscriptomic sequencing. De novo … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 63 publications
(85 reference statements)
0
16
0
Order By: Relevance
“…One of the features in nidovirus is the presence of a −1 ribosomal shifting site, at which the ribosome shifts from ORF1a to ORF1b and produces a fused ORF1ab polypeptide. Within LH1-2018, the frameshift slippery sequence was 5′-GGGUUUU-3′, followed by a stem-loop stimulatory structure [ 8 ]. The same slippery sequence 5′-G 14925 GGUUUU 14931 -3′ and downstream stem-loop structure were found in the ORF1a of Mr-18, and the fused ORF1ab (7797 aa) had a 98.17% nucleotide sequence identity to that of LH1-2018.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the features in nidovirus is the presence of a −1 ribosomal shifting site, at which the ribosome shifts from ORF1a to ORF1b and produces a fused ORF1ab polypeptide. Within LH1-2018, the frameshift slippery sequence was 5′-GGGUUUU-3′, followed by a stem-loop stimulatory structure [ 8 ]. The same slippery sequence 5′-G 14925 GGUUUU 14931 -3′ and downstream stem-loop structure were found in the ORF1a of Mr-18, and the fused ORF1ab (7797 aa) had a 98.17% nucleotide sequence identity to that of LH1-2018.…”
Section: Resultsmentioning
confidence: 99%
“…PCR was initiated at 94 °C for 5 min, followed by 30 cycles of 94 °C 30 s, 57 °C 30 s, and 72 °C 30 s, ending at 72 °C for 10 min. Meanwhile, we used the published PCR detection method to detect 13 M. rosenbergii [ 8 ]. The reverse transcription process was performed as described earlier.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the emerging trend in virology, recently described nidoviruses have been discovered by bioinformatics analysis of next or third generation sequencing data from meta-genomic andtranscriptomics studies of diverse specimens [6,7,[21][22][23][24][25][26][27][28][29][30][31][32][33][34]. These data sets are composed of overlapping sequence fragments of variable lengths (so-called reads) of various origins that can be assembled into contigs, some of which may represent full-length or partial viral genomes.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggest, based on their analysis, that these posalike viruses may represent a new virus family within the order Pircornavirales , and they may have come from parasites infecting the guts of mammals and other animals. Also regarding viruses from invertebrates, in the next article Hooper et al [ 22 ] investigated a mass mortality event of giant freshwater prawn ( Macrobrachium rosenbergii ) larvae in Bangladesh. Using metatranscriptomic sequencing, the authors identified a new virus species within the Nidovirales order, baptized as Macrobrachium rosenbergii golda virus.…”
mentioning
confidence: 99%